Buckwheat Secondary Metabolites: Potential Antifungal Agents - Koval, Daniel; Plocková, Milada; Kyselka, Jan; Skřivan, Pavel; Sluková, Marcela; Horáčková, Šárka (Journal of agricultural and food chemistry, 2020)
Research groups have put significant emphasis on the evaluation of nutritional, health-promoting, and other biological activities of secondary metabolites from buckwheat. Among these phytochemicals, phenolic and lipophilic antioxidants, particularly, phenolic acids, flavonoids, and tocopherols, have been the focus of the latest studies since antioxidant activity has recently been associated with the possibility of inhibiting fungal growth and mycotoxin biosynthesis. The mycotoxin contamination of cereal and pseudocereal grains caused primarily by Fusarium, Penicillium, and Aspergillus species poses a significant hazard to human health. Therefore, efforts to examine the involvement of plant antioxidants in the biosynthesis of mycotoxins at the transcriptional level have emerged. In addition, hydrophobic interactions of buckwheat phenolics with cell membranes could also explain their capacity to reduce fungal development. Eventually, possibilities of enhancing the biological activity of cereal and pseudocereal phytochemicals have been studied, and sourdough fermentation has been proposed as an efficient method to increase antioxidant activities. This effect could result in an increased antifungal effects of sourdough and bakery products. This review reports the main advances in research on buckwheat phenolics and other antioxidant phytochemicals, highlighting possible mechanisms of action and processes that could improve their biological activities.
Keywords: semena rostlinná; nemoci rostlin; Fungi; rostlinné extrakty; sekundární metabolismus; průmyslové fungicidy; houby; Plant Diseases; Phenols; Fungicides, Industrial; lidé; Plant Extracts; Secondary Metabolism; fenoly; Humans; Fagopyrum; Seeds